Determination of Proximate Composition of N.Sativa L. Seeds and its Effective Role in Improving Lipid Profile among Hyperlipidemic Women - Rida Zanib, Shahnai Basharat, Tara Khursheed, Zainab Gulzar, Muhammad Shaheer, Sakina Fatima, Zarnain Ali Shah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the proximate composition of Nigella sativa L. and its hypolipidemic effect on blood lipid profile among hyperlipidemic women. Methodology: To determine the proximate composition of nigella sativa seed the kjeldhah method, soxhlet extraction using petroleum ether and AOAC procedure were used. To determine hypolipidemic impact a total of 64 mild to moderate hyperlipidemic women aged 25-35 years were selected for the 8 weeks of study. The sample was selected from the university of Lahore teaching hospital, Lahore. After removing physical contaminants like dirt, dust and foreign grains black seeds were air drayed. After drying seeds were ground into fine powder by using commercial blender. Each capsule was prepare containing 500 mg powder of N. Sativa, and transfer them in air tight jars. After screening the participants of experimental group were advised to use 2 capsule Nigella sativa supplement before breakfast and two capsules in the afternoon prior to their meal for 8 weeks .Participants were also be advised to follow the given 7-day diet plan for 8 weeks. The anthropometric measurements, biochemical evaluation (lipid profile) and dietary intake data were collected. Results: The mean age group of Hyperlipidemic patients enrolled in study was 32.5 ± 0.34 years. There was a significant reduction in Low density lipoprotein (LDL) Total Cholesterol levels and Triglycerides levels with p-value less than 0.05. High density lipoprotein levels were also improved from 49.5±8.38mg/dl to 51.81±10.21 mg/dl. Conclusion: The study concluded that Nigella sativa L. seed powder supplementation showed a significant improvement in lipid profile of hyperlipidemic patients. The study found an increase in high density lipoprotein among patients.